INFLUENCE OF CRUDE EXTRACTS OF ENDOPHYTES FROM Luehea divaricata (MALVALES; TILIACEAE) ON THE IN VITRO DEVELOPMENT OF Diatraea saccharalis (LEPIDOPTERA; CRAMBIDAE) LARVAE - Targa, Suzete Elaine Mazzoni; Orlandelli, Ravely Casarotti; Wenzel, Juliana Bernardi; Conte, Hélio; Pamphile, João Alencar (SaBios-Revista de Saúde e Biologia, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> One of the main pests of sugarcane is the sugarcane borer (Diatraea saccharalis), that causes direct and indirect damage to this plant. Chemical defensives have been used, although the biological control of pests is the best to be used. These chemical defensives have failed to control plant diseases, generating environmental pollution and affecting human health. Thus, is observed a growing interest in biological control methods based on the use of microorganisms, among them the endophytes, which colonize the interior of plant protecting it against pests and pathogens, directly or indirectly by the production of metabolites, that may be used as an alternative method for biological control. Studies have shown that endophytic fungi isolated from the medicinal plant Luehea divaricata showed to be potent to control phytopathogenic fungi and human pathogenic bacteria. In the present study, the potential of crude extracts of two endophytes from L. divaricata was assessed in order to verify their influence in the in vitro development of larvae of sugarcane borer. To this objective, we used an explanatory and qualitative research with a completely randomized design. As results, a further unrest in the fungal-treated larvae was observed, as well as, the absence of pupal stage had occurred, in comparison with control larvae. <!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> RESUMO Uma das principais pragas da cana-de-açúcar é a broca-da-cana (Diatraea saccharalis), que causa danos diretos e indiretos para esta planta. Defensivos químicos ainda têm sido usados, embora o controle biológico de pragas seja o mais indicado. Esses inseticidas químicos têm falhado no controle de doenças de plantas, gerando poluição ambiental e afetando a saúde humana. Assim, é observado um aumento no interesse por métodos de controle biológico baseados no uso de microorganismos, entre eles, os endófitos, que colonizam o interior de plantas protegendo-as contra pragas e patógenos, direta ou indiretamente pela produção de metabólitos, que podem ser usados como método alternativo para o controle biológico. Estudos apontam que fungos endofíticos isolados da planta medicinal Luehea divaricata mostraram-se potentes para o controle de fungos fitopatogênicos e bactérias patogênicas a humanos. O presente estudo teve por objetivo avaliar o potencial de extratos brutos de dois endófitos de L. divaricata para verificar sua influência no desenvolvimento in vitro de largartas da broca-da-cana. Para tanto, utilizou-se de uma pesquisa explicativa, qualitativa, com um delineamento experimental inteiramente casualizado. Como resultado, uma maior agitação das lagartas tratadas foi observada, bem como, ocorreu a ausência de empupamento em relação às lagartas controle.